Outcome of patients with Fanconi anemia developing myelodysplasia and acute leukemia who received allogeneic hematopoietic stem cell transplantation: A retrospective analysis on behalf of EBMT group. Issue 7 (21st April 2020) - Giardino, Stefano; de Latour, Regis P.; Aljurf, Mahmoud; Eikema, Dirk‐Jan; Bosman, Paul; Bertrand, Yves; Tbakhi, Abdelghani; Holter, Wolfgang; Bornhäuser, Martin; Rössig, Claudia; Burkhardt, Birgit; Zecca, Marco; et al.
Abstract: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is curative for bone marrow failure in patients with Fanconi anemia (FA), but the presence of a malignant transformation is associated with a poor prognosis and the management of these patients is still challenging. We analyzed outcome of 74 FA patients with a diagnosis of myelodysplastic syndrome (n = 35), acute leukemia (n = 35) or with cytogenetic abnormalities (n = 4), who underwent allo‐HSCT from 1999 to 2016 in EBMT network. Type of diagnosis, pre‐HSCT cytoreductive therapies and related toxicities, disease status pre‐HSCT, donor type, and conditioning regimen were considered as main variables potentially influencing outcome. The 5‐year OS and EFS were 42% (30‐53%) and 39% (27‐51%), respectively. Patients transplanted in CR showed better OS compared with those transplanted in presence of an active malignant disease (OS:71%[48‐95] vs 37% [24‐50], P = .04), while none of the other variables considered had an impact. Twenty‐two patients received pre‐HSCT cytoreduction and 9/22 showed a grade 3‐4 toxicity, without any lethal event or negative influence on survival after HSCT(OS:toxicity pre‐HSCT 48% [20‐75%] vs no‐toxicity 51% [25‐78%], P = .98). The cumulative incidence of day‐100 grade II‐IV a‐GvHD and of 5‐year c‐GvHD were 38% (26‐50%) and 40% (28‐52%). Non‐relapse‐related mortality and incidence of relapse at 5‐years were 40% (29‐52%) and 21% (11‐30%) respectively, without any significant impact of the tested variables. Causes of death were transplant‐related events in most patients (34 out of the 42 deaths, 81%). This analysis confirms the poor outcome of transformed FA patients and identifies the importance of achieving CR pre‐HSCT, suggesting that, in a newly diagnosed transformed FA patient, a cytoreductive approach pre‐HSCT should be considered if a donor have been secured.